Brain Mechanisms of Abnormal Temperature Perception in Cold Allodynia induced by Ciguatoxin - Eisenblätter, Anneka; Lewis, Richard; Dörfler, Arnd; Forster, Clemens; Zimmermann, Katharina (Annals of Neurology, 2016)
Cold allodynia occurs as a major symptom of neuropathic pain states. It remains poorly treated with current analgesics. Ciguatoxins (CTXs), ichthyosarcotoxins that cause ciguatera, produce a large peripheral sensitization to dynamic cold stimuli in A?-fibers by activating sodium channels without producing heat or mechanical allodynia. We used CTXs as surrogate model of cold allodynia to dissect the framework of cold allodynia activated central pain pathways.Reversible cold allodynia was induced in healthy male volunteers by shallow intracutaneous injection of low nM concentrations of CTX into the dorsal skin of the forefoot. Cold and warm stimuli were delivered to the treated and the control site using a peltier driven thermotest device. Functional Magnetic Resonance Imaging (fMRI) scans were acquired with a 3 Tesla MRI scanner using a blood-oxygen-level-dependent (BOLD) protocol.The CTX-induced substantial peripheral sensitization to cooling stimuli in A?-fibers is particularly retrieved in BOLD changes due to dynamic temperature changes and less during constant cooling. Brain areas which responded during cold allodynia were always located bilateral and appeared in the medial insula, the medial cingulate cortex, the secondary somatosensory cortex, in frontal areas and the cerebellum. While these areas produced also changes in BOLD-signal during the dynamic warming stimulus on the control site they remained silent during the warming stimuli on the injected site.We describe the defining feature of the cold allodynia pain percept in the human brain and illustrate why ciguatera sufferers often report a perceptual temperature reversal. This article is protected by copyright. All rights reserved.
EVALuna2:16742

Ciguatera fish poisoning: a first epidemic in Germany highlights an increasing risk for European countries - Mattei, Cesar; Vetter, Irina; Eisenblätter, Anneka; Krock, Bernd; Ebbecke, Martin; Desel, Herbert; Zimmermann, Katharina (Toxicon, 2014)
Toxin-producing microalgae are thriving worldwide due to coral reef destruction and global warming with major consequences on ecosystems, international trade and human health. Microalgae belonging to the family of flagellate protists, in particular dinoflagellates, secrete a variety of high-molecular-weight polyether toxins that accumulate through the marine food chain to cause disease in humans by acting as sodium channel activator toxins; ciguatera is the most frequent seafood-borne illness worldwide with 50,000 to 500,000 global incidences per annum and is usually limited to endemic areas located between 35° northern and 35° southern latitude. The rising global incidence frequency renders it a major human health problem, because no curative treatment is available yet and reliable detection assays are lacking. During the last decade ciguatera has increasingly become endemic in previously unaffected areas for two reasons: first global warming has contributed to the emergence of dinoflagellate species in subtropical and even temperate regions that previously had been constrained to tropical areas and second: in Europe globalization of fishing industry and tourism has led to a progressive increase in the number of ciguatera cases and a lack of awareness among medical personnel contributes to under-reporting. We review, through a recent ciguatera outbreak in Germany, the risk for ciguatera poisoning in Europe and highlight characteristic symptoms, current knowledge about disease pathomechanisms and treatment options.
EVALuna2:2368

Imported tropical fish causes ciguatera fish poisoning in Germany - Zimmermann, Katharina; Eisenblätter, Anneka; Vetter, Irina; Ebbecke, Martin; Friedemann, Miriam; Desel, Herbert (Deutsche Medizinische Wochenschrift, 2015)
Ciguatera is a seafood-borne illness caused by consumption of tropical fish contaminated with ciguatoxins, lipophilic polyethers that are produced in benthic dinoflagellates and accumulate through the marine food chain. Ciguatera cases in Europe usually occur in travellers returning from tropical and subtropical regions of the Pacific and Carribean, where ciguatera is endemic. In 2012, several cases of ciguatera occurred in Germany due to sale of contaminated fish products originating from the Indian Ocean. Although the symptomatology in these cases were typical of ciguatera, with patients reporting gastrointestinal discomfort including nausea, vomiting and diarrhea as well as neurological effects including widespread intense pruritus, paresthesias, hypothermia or altered temperature sensation and diffuse pain, correct diagnosis was delayed in all cases due to lack of awareness of the treating medical practitioners. In light of increasing global mobility, trade, and occurrence of ciguatoxic fish in previously non-endemic areas, ciguatera should be considered as a possible diagnosis if gastrointestinal and neurological symptoms occur shortly after consumption of fish.
EVALuna2:2486